2022
DOI: 10.5539/ijc.v14n2p8
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth, Structural and Thermal Studies of FeC4H4O6·2.5H2O

Abstract: Single crystals of iron(II) tartrate hemi-pentahydrate, FeC4H4O6·2.5H2O, were grown by the gel method using silica gels. Differential scanning calorimetry, thermogravimetric-differential thermal analysis, and X-ray diffraction measurements were performed on the single crystals. The space group symmetry (orthorhombic P212121) and structural parameters were determined at room temperature. The crystal structure consisted of slightly distorted FeO6 octahedra, C4H4O6 and H2O molecules, C4H4O6–F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Single crystals and polycrystalline aggregates were grown in the gel medium. The polycrystalline aggregates, which were quasi-spherical in shape and green in color, were very similar to those of FeC 4 H 4 O 6 •2.5H 2 O aggregates reported in the previous papers, except for the difference in color (Dhikale, Shitole, Nahire, & Chavan, 2019;Fukami & Tahara, 2022;Mathivanan & Haris, 2013).…”
Section: Crystal Growthsupporting
confidence: 84%
See 4 more Smart Citations
“…Single crystals and polycrystalline aggregates were grown in the gel medium. The polycrystalline aggregates, which were quasi-spherical in shape and green in color, were very similar to those of FeC 4 H 4 O 6 •2.5H 2 O aggregates reported in the previous papers, except for the difference in color (Dhikale, Shitole, Nahire, & Chavan, 2019;Fukami & Tahara, 2022;Mathivanan & Haris, 2013).…”
Section: Crystal Growthsupporting
confidence: 84%
“…The lattice parameters calculated from all observed X-ray reflections showed that the crystal belongs to the orthorhombic system, and the systematic extinctions indicated that the space group is P2 1 2 1 2 1 . The obtained lattice parameters were similar to those of FeC 4 H 4 O 6 •2.5H 2 O 2022). All non-hydrogen atoms were refined anisotropically, and hydrogen atoms located on difference electron density maps were refined isotropically.…”
Section: Structure Determinationmentioning
confidence: 75%
See 3 more Smart Citations